Analysis of Saving Electrical Load Costs With a Hybrid Source of PLN-PLTS 500 Wp - Zuraidah Tharo; Erwin Syahputra; Rahmad Mulyadi (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Short-term and long-term energy needs and consumption in the provision and use of sustainable energy nationally, require strategic directions and steps to achieve. The strategic directions and steps are contained in the National Energy Policy (KEN) which has been stipulated in PP. 79 of 2014 concerning KEN. KEN is an implementation of the mandate of Law no. 30 of 2007 concerning Energy. Apart from being used as primary energy for power generation, NRE is also being developed as energy that is used directly by the user sector. At this time the type of EBT that is most widely used by users is PLTS, in addition to its simple construction and heat sources can be obtained anywhere, this is also the government's recommendation to achieve the PLTS development target. In fact, until now, consumers are still very less willing to use PLTS in meeting their electrical energy needs, this is due to several problems, including the high cost of PLTS construction, besides that the material costs are also relatively expensive. In this study, an overview of the calculation of how much cost can be saved or saved if the energy source used is a Hybrid between PLN and PLTS 500 Wp which is used alternately in supplying the electrical load of a simple house. with specifications of 2 solar panels of 250 wp each, 2 batteries of 100 Ah each, 130 solar panel control and 1300 watt inverter. The cost of electricity charges paid monthly before using PLTS Roof ranges from 300 to 400 thousand rupiah, After using PLTS Roof, the monthly electricity costs are 200 to 300 thousand rupiah, the average monthly savings is 100 thousand rupiah, if you take into account the investment costs will return in 1 year, the average material life of PLTS is around 20 years. The cost savings in electricity costs are around Rp. 22.800.000,- in 20 years. Economically, this value is still very small, but it has succeeded in saving electricity costs per month, and increasing the use of Renewable Energy